2000
DOI: 10.1136/bjo.84.4.364
|View full text |Cite
|
Sign up to set email alerts
|

COL2A1 exon 2 mutations: relevance to the Stickler and Wagner syndromes

Abstract: (Br J Ophthalmol 2000;84:364-371)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(99 citation statements)
references
References 28 publications
2
93
0
4
Order By: Relevance
“…Our recent studies have shown that the families, studied by Snead et al 9 and additional sporadic cases with the membraneous anomaly, all have mutations in COL2A1. 10,11 In nearly all cases these, via a variety of different types of mutations, lead to premature termination condons and haploinsufficiency of type II collagen. Analysis of illegitimate COL2A1 mRNAs indicated that mutant transcripts were degraded by a process known as nonsense mediated decay (NMD).…”
Section: Stickler Syndrome (Mim 108300 604841)mentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent studies have shown that the families, studied by Snead et al 9 and additional sporadic cases with the membraneous anomaly, all have mutations in COL2A1. 10,11 In nearly all cases these, via a variety of different types of mutations, lead to premature termination condons and haploinsufficiency of type II collagen. Analysis of illegitimate COL2A1 mRNAs indicated that mutant transcripts were degraded by a process known as nonsense mediated decay (NMD).…”
Section: Stickler Syndrome (Mim 108300 604841)mentioning
confidence: 99%
“…17,18 Mutations in this exon are therefore effectively removed from cartilage tissue, resulting in a predominantly ocular Stickler syndrome phenotype. 10 Patients with this phenotype may have been mistaken for Wagner syndrome (see below). However all had the congenital membraneous anomaly and were clearly variants of Stickler syndrome rather than Wagner syndrome.…”
Section: Stickler Syndrome (Mim 108300 604841)mentioning
confidence: 99%
“…19,20 A variety of mutations spread throughout the entire COL2A1 gene have been identified in families with the Stickler syndrome. [21][22][23][24][25][26][27][28][29][30][31] Most of the Stickler COL2A1 mutations noted to date result in the introduction of a premature stop codon, suggesting that the phenotype usually results from a quantitative defect in type II procollagen biosynthesis either because of the nonsense-mediated mRNA decay pathway or failure of chain association. COL2A1 mutations associated with phenotypes more severe than the Stickler syndrome such as achondrogenesis type II, hypochondrogenesis, spondyloepiphyseal dysplasia congenita, and Kniest dysplasia result from missense mutations that cause defects in the structure of type II collagen protein.…”
mentioning
confidence: 99%
“…Porém, a dificuldade no diagnóstico diferencial com outras alterações genéticas como a síndrome de Marshall ou fenótipo Marshall/ Stickler (21) , síndrome de Wagner (20,23) , alta miopia familial (26) , subestima o número de pacientes com síndrome de Stickler.…”
Section: Discussionunclassified
“…Devido às várias mutações descritas na literatura, novos genes provavelmente relacionados à SS e a dificuldade clínica no diagnóstico diferencial, muitos profissionais médicos não fazem o diagnóstico correto dessa síndrome (7)(8)(20)(21)(22)(23)(24) .…”
Section: Introductionunclassified